Earnings management to avoid delisting from a stock market - Aleš Čornanič; Jiří Novák (Charles University in Prague, Institute of Economic Studies (IES), 2015)
We show that firms 'in danger' of being delisted from a stock market (NASDAQ) report higher performance-adjusted discretionary accruals and the inflated accruals are associated with an increased likelihood of maintained listing. Accruals of firms 'in danger' are less positive in fiscal quarters audited by a Big-4 auditor and after the implementation of SOX. In contrast, accruals are higher for firms that benefit most from public listing and for firms with good future prospects. This suggests that managers consider reputation and litigation risk associated with earnings management and they manage earnings only when they believe the firm will recover in near future. The market can thus interpret discretionary accruals as a signal revealing managers' private information about firm quality. Consistent with the signaling explanation we observe a stronger stock price reaction on the announcement of earnings that contain large accruals in threatened firms.
Keywords: G34; M41; M42; M48; 330; Delisting; earnings management; discretionary accruals; insider trading; reverse stock split; audit; Sarbanes-Oxley Act